Establishment of a New Hyperglycemic Obesity Cardiac Dysfunction Mouse Model with Triacsin C - ZHAO Xiaona; WANG Peng; YE Maoqing; QU Xinkai (Shiyan dongwu yu bijiao yixue)
Objective This study aims to establish a novel hyperglycemic obesity mouse model by utilizing Triacsin C, an inhibitor of acyl-CoA synthetase long-chain family member 1 (ACSL1), combined with a high-fat diet, to simulate the changes in adipose tissue and cardiac function observed in patients with obesity-related type 2 diabetes.MethodsTwenty adult SPF-grade male C57BL/6J mice were randomly divided into two groups: the Control group (injected intraperitoneally with citric acid-sodium citrate buffer, Con group) and the TC group (injected intraperitoneally with Triacsin C, TC group). After four consecutive weeks of intraperitoneal injections, both groups were fed high-fat diets. Body weight and glucose tolerance of the mice were assessed every eight weeks. The models were considered successful if fasting blood glucose exceeded 8 mmol/L or blood glucose was above 15 mmol/L two hours after glucose injection. Cardiac function, including ventricular end-diastolic diameter (LVEDD), left ventricular end systolic diameter (LVESD), end-diastolic interventricular septal thickness (EDIVS), left ventricular ejection fraction (LVEF), and left ventricular short-axis fractional shortening (FS), was measured by echocardiography. HE staining was used to detect the changes in epididymal white adipose tissue (WAT) and brown adipose tissue (BAT). Immunofluorescence technology was used to analyze changes in CD31 and UCP1 in BAT. ACSL1 expression in myocardial tissue was tested by Western blotting.ResultsThe fasting blood glucose levels were (8.14±1.43) mmol/L in the Con group and (8.18±0.85) mmol/L in the TC group (P>0.05) , and the 2-hour postprandial blood glucose levels were (19.8±4.01) mmol/L in the Con group and (22.60±3.97) mmol/L in the TC group (P<0.05). This indicated that both groups of diabetic mouse models were successfully established. Compared to the Con group, the TC group showed poor glucose tolerance; significant decreases in LVEDD, LVEF and FS (P<0.05); significant increases in WAT and BAT areas (P<0.05); significant decreases in CD31 and UCP1 expression (P<0.05); and a significant decrease in the expression of ACSL1 in myocardial tissues (P<0.05).ConclusionCompared with the high-fat diet-induced type 2 diabetes model, the new hyperglycemic obesity and cardiac dysfunction mouse model, created by the combination of Triacsin C and a high-fat diet, is feasible and allows for easier observation of brown adipose tissue whitening, insulin resistance and cardiac dysfunction.